2015
DOI: 10.4149/neo_2015_094
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 167 healthy sibling donors after peripheral blood stem cell mobilization with G-CSF 16μg/kg/day: efficacy and safety

Abstract: Mobilization of peripheral blood stem cells (PBSC) using the granulocyte colony-stimulating factor (G-CSF) has enabled the collection even from older donors and those with comorbidities. Several clinical parameters have been reported to predict the success of PBSC mobilization.The aim of our study was to evaluate the safety of PBSC donation in a cohort of 167 sibling donors after mobilization with G-CSF 16 μg/kg/day for 5 days during short-and long term follow-up and to analyse the efficacy, toxicity and facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Treatment with granulocyte colony-stimulating factor (G-CSF) is commonly used for mobilization of peripheral blood stem cells in healthy donors ( 11 , 12 ). G-CSF has several immunomodulatory effects, and for a detailed discussion and additional references we refer to a recent review ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with granulocyte colony-stimulating factor (G-CSF) is commonly used for mobilization of peripheral blood stem cells in healthy donors ( 11 , 12 ). G-CSF has several immunomodulatory effects, and for a detailed discussion and additional references we refer to a recent review ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Although several studies in adult donors have not demonstrated any increased long-term complications such as increased cancer risk after short-term G-CSF administration for PBSC, sufficient long-term studies in children addressing this issue have not been performed. [14][15][16] The procedure of PBSC collection in children has the potential of causing pain related to G-CSF administration (site of administration and/or bone pain), the risks associated with central venous catheter (CVC) placement, the occurrence of hypocalcemia during apheresis, and the risk of cardiovascular complications related to hypovolemia. In addition, children with less than 20kg may be exposed to heterologous red blood cells to prime an apheresis circuit of the machine.…”
Section: Peripheral Blood Progenitor Cell (Pbpc) Collectionmentioning
confidence: 99%
“…Minimally manipulated tissue processing results in a characterized product, that is available as an “off-the-shelf” cell and matrix product for easy use in practice and avoids some of the limitations with currently reported tissue sources. These limitations for current sources, that are either not a limitation or much reduced limitation for dental pulp, include, for differentiated tissue such as skin and blood, low stem cell yields that often require extraction (34, 35) or mobilization (36), respectively. Umbilical cord and amnion can be contaminated at birth increasing the potential risk of infection in the stem cell harvests.…”
Section: Introductionmentioning
confidence: 99%